The impact of plant product harvesting on Derre Miombo woodlands, Mozambique / by Maria Cruz. - Cruz, Maria (Maria Regina Torres) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScFor)--Stellenbosch University, 2002.